Contraceptive use in Latin America and the Caribbean with a focus on long-acting reversible contraceptives: prevalence and inequalities in 23 countries. Issue 2 (February 2019) - Ponce de Leon, Rodolfo Gomez; Ewerling, Fernanda; Serruya, Suzanne Jacob; Silveira, Mariangela F; Sanhueza, Antonio; Moazzam, Ali; Becerra-Posada, Francisco; Coll, Carolina V N; Hellwig, Franciele; Victora, Cesar G; Barros, Aluisio J D
Summary: Background: The rise in contraceptive use has largely been driven by short-acting methods of contraception, despite the high effectiveness of long-acting reversible contraceptives. Several countries in Latin America and the Caribbean have made important progress increasing the use of modern contraceptives, but important inequalities remain. We assessed the prevalence and demand for modern contraceptive use in Latin America and the Caribbean with data from national health surveys. Methods: Our data sources included demographic and health surveys, multiple indicator cluster surveys, and reproductive health surveys carried out since 2004 in 23 countries of Latin America and the Caribbean. Analyses were based on sexually active women aged 15–49 years irrespective of marital status, except in Argentina and Brazil, where analyses were restricted to women who were married or in a union. We calculated contraceptive prevalence and demand for family planning satisfied. Contraceptive prevalence was defined as the percentage of sexually active women aged 15–49 years who (or whose partners) were using a contraceptive method at the time of the survey. Demand for family planning satisfied was defined as the proportion of women in need of contraception who were using a contraceptive method at the time of the survey. We separated survey data for modern contraceptive use by type of contraception used (long-acting, short-acting, or permanent). We also stratified survey data by wealth, area of residence, education, ethnicity, age, and a combination of wealth and area of residence. Wealth-related absolute and relative inequalities were estimated both for contraceptive prevalence and demand for family planning satisfied. Findings: We report on surveys from 23 countries in Latin America and the Caribbean, analysing a sample of 212 573 women. The lowest modern contraceptive prevalence was observed in Haiti (31·3%) and Bolivia (34·6%); inequalities were wide in Bolivia, but almost non-existent in Haiti. Brazil, Colombia, Costa Rica, Cuba, and Paraguay had over 70% of modern contraceptive prevalence with low absolute inequalities. Use of long-acting reversible contraceptives was below 10% in 17 of the 23 countries. Only Cuba, Colombia, Mexico, Ecuador, Paraguay, and Trinidad and Tobago had more than 10% of women adopting long-acting contraceptive methods. Mexico was the only country in which long-acting contraceptive methods were more frequently used than short-acting methods. Young women aged 15–17 years, indigenous women, those in lower wealth quintiles, those living in rural areas, and those without education showed particularly low use of long-acting reversible contraceptives. Interpretation: Long-acting reversible contraceptives are seldom used in Latin America and the Caribbean. Because of their high effectiveness, convenience, and ease of continuation, availability of long-acting reversible contraceptives should be expanded and their use promoted, including among young and nulliparous women. In addition to suitable family planning services, information and counselling should be provided to women on a personal basis. Funding: Wellcome Trust, Pan American Health Organization.